Dynamic mode decomposition of rotorcraft blade tip vortex in hovering state - Wenjie Kong; Hai Du; Qinlin Zhang; Qixuan Li; Xinyue Lv; Lianbin Zhou; Weiguo Zhang (AIP Advances, 2020)
The flow field structure of a rotorcraft is complex; specifically, the rotor tip vortex structure has a great influence on the rotor performance. Therefore, in this paper, the evolution characteristics of rotor tip vortices and the dynamic mode decomposition (DMD) of rotor tip vortices in a rotor hovering state are studied. Through a time-resolved particle image velocimetry experiment, a comparative study of the blade tip vortex flow field at a fixed rotation speed (1500 rpm) and a collective pitch of 6° and 9° was performed. The method of DMD is used for the reduced-order analysis of the vorticity field of the blade tip vortex in the hovering state. By this method, these important vortex structures are extracted and discussed; meanwhile, the future flow field is also reconstructed. The results of flow visualization indicate that the trajectory of the blade tip vortex is moving down the axis, while moving toward the hub in the radial direction in the hovering state. The results of DMD analysis show that during the evolution of the blade tip vortex, different modes have different contributions to the rotor as a whole. In addition, the larger the collective pitch, the larger the modal coefficient amplitude and the slower the stabilization speed.